Developing intercultural awareness using digital storytelling - Ribeiro, Sandra (2017)
Higher Education mirrors the shifting nature of society and work. Mobility may provide unparalleled learning opportunities for all stakeholders; however, in order to live and work in plural societies as socially responsible and intercultural knowledgeable citizens, intercultural awareness and intercultural communication skills need to be mastered. In parallel, the relevance of a digital agenda and the studies that attest to the positive student engagement brought about by the inclusion of information and communication technologies (ICT) across all grade levels push educators to seek and incorporate technology-based learning and teaching strategies. Digital Storytelling was implemented in an undergraduate degree in Business Communication, where students discuss and reflect on key issues in Intercultural Communication. Our case study draws on the qualitative analysis of a questionnaire, which intended to understand student perceptions regarding an assignment where they are asked to create Digital Stories and consider on the their own reflection process regarding intercultural differences and communicating across cultures. Our analysis of the 140 questionnaires revealed that Digital Storytelling was able to engage students in a serious and productive debate revolving around technology-enhanced learning and cultural differences, empowering them to construct new personal and group meanings and improve their intercultural awareness.